7(7-x)=4(x-6)

Simple and best practice solution for 7(7-x)=4(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7-x)=4(x-6) equation:


Simplifying
7(7 + -1x) = 4(x + -6)
(7 * 7 + -1x * 7) = 4(x + -6)
(49 + -7x) = 4(x + -6)

Reorder the terms:
49 + -7x = 4(-6 + x)
49 + -7x = (-6 * 4 + x * 4)
49 + -7x = (-24 + 4x)

Solving
49 + -7x = -24 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
49 + -7x + -4x = -24 + 4x + -4x

Combine like terms: -7x + -4x = -11x
49 + -11x = -24 + 4x + -4x

Combine like terms: 4x + -4x = 0
49 + -11x = -24 + 0
49 + -11x = -24

Add '-49' to each side of the equation.
49 + -49 + -11x = -24 + -49

Combine like terms: 49 + -49 = 0
0 + -11x = -24 + -49
-11x = -24 + -49

Combine like terms: -24 + -49 = -73
-11x = -73

Divide each side by '-11'.
x = 6.636363636

Simplifying
x = 6.636363636

See similar equations:

| 6=-4+8x | | -12x-9=107 | | 8x+2y=1600 | | 19+x=18 | | -14m-8=98 | | 15-2x=42+x | | D^2+8d-20= | | 3=8x-53 | | -2x+1x= | | 2m(3+4m)+4m= | | 12(x-4)-3=19x-100 | | 0.1t=0.6+0.5t | | A=L(W) | | -9(-7n+1)=-8+4(4n-12) | | -346x=0 | | 125x^3-20x=0 | | 6x-15=x+15+5x | | 100+10j=15j | | 9t+9-3t-7= | | 0=y^2+10y+9 | | 3x-5=7x+x-15 | | 9-4w=-11 | | 5(1+4h)+2h=27 | | 12k+9m-2m-12k= | | 5a+2=3a+2 | | 3+2x=14-3x | | 35.00+0.75x=1.25x | | 3x+16=5-x | | 5h^2-15h-270= | | 2x+3+51=180 | | 2-6(z+1)=4(z-2)+10 | | 2s^2-128= |

Equations solver categories